Perspektiewe vanuit die psigologie en sosiale wetenskappe vir kerklike bediening aan die adolessent. ‘n Ondersoek na die ontwikkeling van die adolessent - Erasmus, J. A. (Verbum et ecclesia, 2002)
In this article meta-theoretical perspectives for youth ministry are presented from the fields of psychology and sociology. In the first place, it is determined what the various psychological development phases of the adolescent are, and how they have to be accounted for in youth ministry. In the second place, it is also determined what the characteristics of the world are in which the adolescent lives, and what their influences are on adolescents.